(Cyclopentadienone)iron Complexes: Synthesis, Mechanism and Applications in Organic Synthesis. Issue 13 (1st June 2021) - Akter, Monalisa; Anbarasan, Pazhamalai
Abstract: (Cyclopentadienone)iron tricarbonyl complexes are catalytically active, inexpensive, easily accessible and air‐stable that are extensively studied as an active pre‐catalyst in homogeneous catalysis. Its versatile catalytic activity arises exclusively due to the presence of a non‐innocent ligand, which can trigger its unique redox properties effectively. These complexes have been employed widely in (transfer)hydrogenation (e. g., reduction of polar multiple bonds, Oppenauer‐type oxidation of alcohols), C−C and C−N bond formation (e. g., reductive aminations, α ‐alkylation of ketones) and other synthetic transformations. In this review, we discuss the remarkable advancement of its various synthetic applications along with synthesis and mechanistic studies, until February 2021. Abstract : (Cyclopentadienone)iron complexes (CPDICs) have emerged as an excellent alternative to precious metal catalysts to accomplish diverse synthetic transformations with high chemo‐ and enantioselectivity, which involve mainly hydrogen transfer mechanism. This review is focused on the significant development of CPDICs‐catalyzed homogeneous transformations along with their synthesis and mechanistic insights.